Lipopolysaccharide and monophosphoryl lipid A differentially regulate interleukin-12, gamma interferon, and interleukin-10 mRNA production in murine macrophages. - Salkowski, C A (1997)
Monophosphoryl lipid A (MPL) is a nontoxic derivative of the lipid A region of lipopolysaccharide (LPS) that is being developed as both an adjuvant and prophylactic drug for septic shock. We compared the ability of LPS and MPL to induce interleukin-10 (IL-10), IL-12 p35, IL-12 p40, gamma interferon (IFN-gamma), glucocorticoid receptor (GR), IL-1 receptor antagonist (IL-1ra), and inducible nitric oxide synthase mRNA expression in murine peritoneal macrophages. These genes were chosen for their ability to positively or negatively regulate the host immune response and thus for their potential involvement in MPL-induced adjuvanticity or in its ability to protect against sepsis. LPS was a more potent inducer of IL-12 p35, IL-12 p40, and IFN-gamma mRNA, as well as of IL-12 protein, than MPL. In contrast, MPL induced higher levels of IL-10 mRNA than did LPS from 1 to 1,000 ng/ml. In general, MPL was not a more potent inducer of negative regulatory genes, since MPL and LPS induced similar levels of GR and IL-1ra mRNA. Addition of anti-IL-10 antibody to cultures increased the induction of MPL-induced IL-12 p35, IL-12 p40, and IFN-gamma mRNA, suggesting that the enhanced production of IL-10 by MPL-stimulated macrophages contributes to decreased production of mRNA for IL-12 (p35 and p40) and IFN-gamma. Conversely, the addition of exogenous IL-10 to LPS-treated macrophages reduced the mRNA expression of these cytokine genes. These studies suggest that enhanced production of IL-10 by MPL-stimulated macrophages may contribute to the reduced toxicity of MPL through its negative action on induction of cytokines shown to enhance endotoxicity.